A study to evaluate antioxidant and hepatoprotective activity of aqueous extract of roots of Valeriana wallichii in CCl4 induced hepatotoxicity in rats - Syed, Shariq Naeem; Rizvi, Waseem; Kumar, Anil; Khan, Aijaz Ahmad; Moin, Shagufta; Ahsan, Akif (International Journal of Basic & Clinical Pharmacology, 2017)
Background: Drugs for liver ailments have been important in research, but still the number of drugs acting on various hepatic diseases is very limited. This study, for the first time, evaluates the hepatoprotective activity of aqueous extract of the roots of Valeriana Wallichii in albino rats. Methods: The hepatotoxicity was induced by CCl4. Animals were divided into 5 groups of 6 animals each. Group I (Normal control) was given only distilled water. Group II (Negative control)was administered CCl4 for 7 days while Group III (Positive control) was given silymarin and CCl4 for 7 days. The test groups (Group IV & V) were given an aqueous extract of roots of V. Wallichii in a dose of 300 mg and 500 mg/kg, respectively. The animals were sacrificed on 8 days and blood was collected for biochemical analysis (aspartate aminotransferase [AST], alanine transaminase (ALT) and alkaline phosphatase). Liver tissue was extracted for histopathological examination and in vivo antioxidant tests Catalase [CAT], glutathione and malondialdehyde. The extract was also subjected to in vitro antioxidant tests (Total reducing power and total phenolic content). Results: The test extracts in the dose of 500 mg/kg were shown a significant decrease in the levels of AST and ALT (p>0.05) and CAT activity. 300 mg/kg dose of extract showed minimal hepatoprotection. The findings were confirmatory to histopathology. Conclusion: The aqueous extract of roots of V. Wallichii in a dose of 500 mg/kg offers partial protection against hepatotoxicity produced by CCl4 in albino rats.